Stigma? What stigma? A contribution to the debate on financial market effects of IMF lending - Beatrice Scheubel; Andrea Tafuro; Benjamin Vonessen (European Central Bank (ECB), 2018)
In the policy debate on the effectiveness of the Global Financial Safety Net, concerns have been raised that expectations of adverse effects of IMF programmes may deter countries from asking for an IMF programme when they need one, a form of "IMF stigma". We explore the existence of IMF financial market stigma using monthly data by estimating how and to which extent adverse market reactions to a programme materialise and how past experience with adverse market reactions affects subsequent IMF programme participation. Our results, derived with event history techniques and propensity score matching, indicate no role for "IMF stigma" stemming from the fear of adverse market movements. Instead, we find evidence of "IMF recidivism" driven by adverse selection and IMF conditionality.
Keywords: E02; F32; F33; F34; 330; Capital flows; IMF conditionality; IMF recidivism; Global Financial Safety Net; Asian Crisis; treasury bill rates